Manajemen Strategik Pusat Sumber Belajar di Era Revolusi Industri 4.0 - Pusvyta Sari (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Abstract This article reviews the importance of strategic management of learning resource centers in the era of the industrial revolution 4.0. The development of information and communication technology has led to new sources of learning in digital form, the use of computers, internet networks and new ways of learning that can do in anywhere at any time. These learning resources require adequate knowledge and skills. With strategic management, hopefully that learning resource centers can answer the challenges of the industrial revolution 4.0 to provide the learning resources needed while helping students and instructors to be able to use them optimally. Keywords: strategic manajement of learning recource center, era of the industrial revolution 4.0 Abstrak Artikel ini mengulas mengenai pentingnya manajemen strategik pusat sumber belajar di era revolusi industri 4.0. Perkembangan teknologi informasi dan komunikasi memunculkan sumber-sumber belajar baru dalam bentuk digital, penggunaan komputer, jaringan internet serta cara belajar baru yang bisa dilakukan dimana saja kapan saja. Sumber belajar tersebut membutuhkan pengetahuan sekaligus keterampilan yang memadai. Dengan manajemen strategik diharapkan pusat sumber belajar dapat menjawab tantangan revolusi industri 4.0 untuk menyediakan sumber belajar yang dibutuhkan sekaligus membantu peserta didik dan pengajar untuk bisa memanfaatkannya dengan optimal. Kata kunci: Manajemen strategik Pusat Sumber Belajar, Era Revolusi Industri 4.0